Genetic heterogeneity of Escherichia coli isolated from pasteurized milk in State of Paraná, Brazil - Oltramari, Karine; Cardoso, Rosilene Fressati; Patussi, Eliana Valeria; Barreto Santos, Adolfo Carlos [UNESP]; Graton Mikcha, Jane Martha (Universidade de São Paulo, Conjunto Químicas, 2014)
Food contamination caused by enteric pathogens is a major cause of diarrheal disease worldwide, resulting in high morbidity and mortality and significant economic losses. Bacteria are important agents of foodborne diseases, particularly diarrheagenic Escherichia coli. The present study assessed the genetic diversity and antimicrobial resistance of E. coli isolates from pasteurized milk processed in 21 dairies in northwestern State of Parana, Brazil. The 95 E. coli isolates were subjected to antimicrobial susceptibility testing according to the recommendations of the Clinical and Laboratory Standards Institute and assessed genotypically by Enterobacterial Repetitive Intergenic Consensus-Polymerase Chain Reaction (ERIC-PCR). The highest rate of resistance was observed for cephalothin (55.78%). ERIC-PCR revealed high genetic diversity, clustering the 95 bacterial isolates into 90 different genotypic patterns. These results showed a heterogeneous population of E. coli in milk samples produced in the northwestern region of Parana and the need for good manufacturing practices throughout the processing of pasteurized milk to reduce the risk of foodborne illnesses.

A contaminação de alimentos por patógenos entéricos é uma das principais causas de doenças diarréicas em todo o mundo, resultando em altas taxas de morbidade e mortalidade e perdas econômicas significativas. As bactérias são importantes agentes de doenças de origem alimentar, particularmente Escherichia coli diarreiogênicas. O presente estudo teve como objetivo avaliar a diversidade genética e a resistência a antimicrobianos de E. coli isoladas de leite pasteurizado, processados em 21 laticínios na região noroeste do Paraná - Brasil. Os 95 isolados de E. coli foram submetidos a testes de suscetibilidade aos antimicrobianos de acordo com as recomendações do Clinical and Laboratory Standards Institute e avaliados genotipicamente por ERIC-PCR (Enterobacterial Repetitive Intergenic Consensus - Polymerase Chain Reaction). O principal perfil de resistência encontrado entre os isolados foi resistência à cefalotina (55,78%). ERIC-PCR revelou alta diversidade genética, agrupando os 95 isolados bacterianos em 90 diferentes perfis genotípicos. Estes resultados mostraram uma população heterogênea de E. coli em amostras de leite produzido na região noroeste do Paraná e a necessidade de boas práticas na manipulação de todo o processamento de leite pasteurizado, a fim de reduzir o risco de doenças transmitidas por alimentos.
Keywords: Pasteurized milk/processing; Pasteurized milk/bacterial typing; Pasteurized milk/contamination; Escherichia coli/genetic diversity; Escherichia coli/antimicrobial resistance; Food/microbiological analysis; Leite pasteurizado/processamento; Leite pasteurizado/tipagem bacteriana; Leite pasteurizado/contaminação; Escherichia coli/diversidade genética; Escherichia coli/resistência a antimicrobianos; Alimentos/análise microbiológica